Sexual aggression in adolescence: risky sexual scripts and sexual behaviors = Agresja seksualna w wieku dorastania: ryzykowne skrypty seksualne i zachowania seksualne - Krahé, Barbara (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The present series of studies has examined the sexual scripts that adolescents have for consensual sexual encounters and the extent to which they contain characteristic features that have been linked to the problem of sexual aggression.
Keywords: młodzież; agresja seksualna; skrypty seksualne; aktywność seksualna; wiktymizacja; pornografia; youth; sexual aggression; sexual scripts; sexual activity; victimization; pornography